Processing renewable and waste-based feedstocks with fluid catalytic cracking: Impact on catalytic performance and considerations for improved catalyst design - Mastry, Melissa Clough; Dorazio, Lucas; Fu, James C.; Gómez, Juan Pedro; Sedano, Sergio; Ail, Snehesh S.; Castaldi, Marco J.; Yilmaz, Bilge (Frontiers in Chemistry, 2023)
Refiners around the globe are either considering or are actively replacing a portion of their crude oil inputs originating from fossil sources with alternative sources, including recycled materials (plastics, urban waste, mixed solid waste) and renewable materials (bio-mass waste, vegetable oils). In this paper, we explore such replacement, specifically focusing on the fluid catalytic cracking (FCC) operation. Five pyrolysis oils, obtained from municipal solid waste (MSW) and biogenic material (olive stones/pits), were fully characterized and tested at 10% loading against a standard fluid catalytic cracking (FCC) vacuum gasoil (VGO) feed in a bench scale reactor using an industrially available fluid catalytic cracking catalyst based on ultrastable Y zeolite to simulate fluid catalytic cracking co-processing. Despite having unique feed properties, including high Conradson carbon (e.g., up to 19.41 wt%), water (e.g., up to 5.7 wt%), and contaminants (e.g., up to 227 ppm Cl) in some cases, the five pyrolysis oils gave similar yield patterns as vacuum gasoil. Gasoline was slightly (ca. 1 wt%) higher in all cases and LPG slightly (ca. 1 wt%) lower. Olefinicity in the LPG streams were unchanged, bottoms and light cycle oil (LCO) showed no significant changes, while dry gas was slightly (up to −0.2 wt%) lower. Coke selectivity was also unchanged (maximum −7.7 wt%, relatively), suggesting minimal to no heat balance concerns when co-processing in an industrial fluid catalytic cracking unit. The results demonstrate the applicability of municipal solid waste and biogenic originating pyrolysis oils into a refinery. A catalyst design concept is explored, based on higher rare Earth oxide exchange and/or utilization of ZSM-5 zeolite, that would further minimize the impacts of replacing fossil oils with pyrolysis oils, namely one that shifts the 1% higher gasoline into LPG.